1998
DOI: 10.1177/089124198027001002
|View full text |Cite
|
Sign up to set email alerts
|

Social Class and Parental Attitudes Toward Education

Abstract: This study investigates the impact of social class on parents' attitudes toward their children's education. The results suggest that two concepts—resistance and conformity—are central to understanding parental attitudes toward education and the process by which those attitudes are shaped. The data indicate that the probability parents will conform to or resist the meritocratic ideology of acquiring a college degree to help ensure occupational success tends to depend on parents' social-class background and, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…In the same vein, universityeducated parents recalled their own primary school more positively in terms of the justness and impartially of the treatment which they had received, the quality of instruction, the encouragement, and the usefulness of the learning attained, in contrast to vocationally educated parents (Räty, 2003b; for similar results, see Brantlinger, 1985;Gorman, 1998).…”
Section: Introductionmentioning
confidence: 90%
“…In the same vein, universityeducated parents recalled their own primary school more positively in terms of the justness and impartially of the treatment which they had received, the quality of instruction, the encouragement, and the usefulness of the learning attained, in contrast to vocationally educated parents (Räty, 2003b; for similar results, see Brantlinger, 1985;Gorman, 1998).…”
Section: Introductionmentioning
confidence: 90%
“…Clémance 2001). The predominant notion of intelligence is contested and resisted in the school as well (Gorman 1998). In our scrutiny of the children's drawings, we were therefore also interested in finding potentially critical or polemical elements.…”
Section: Introductionmentioning
confidence: 99%
“…Role models and mentors, early education experiences, and parental involvement in education are influential in creating an atmosphere that values higher education (Akmal & Larsen, 2004;Bempechat, 1990;Gorman, 1998;McLaughlin & Shields, 1987). Many authors have concluded that parental attainment of higher education is the most potent variable in predicting the same in their children (Finnie, Childs, & Wismer, 2011;McMullen, 2013).…”
Section: Institutions Of Higher Learning: the Way Forwardmentioning
confidence: 99%